Characters of William Shakespeare in Translation on Shakespeare in Love Subtitling: A Systemic Functional Linguistic Approach - Diah Supatmiwati (International Conference on Education and Language (ICEL), 2013)
This thesis explores William Shakespeare characters in one cinematic production of Marc Norman & Tom StoppardShakespeare in Love (SIL) and the realization in Indonesian version. The main problem is to discuss the WS’ characters construction through language found in ST and the realization in TT with a specific objective to analyze how the manner of William Shakespeare (WS) is constructed, through the way he models his experiences of both internal and external world in language. This is qualitative and quantitative research which is based on text analysis. A descriptive and comparative analysis is conducted to compare both analyzed texts. The research method goes through 3 main stages starting from data classification, analysis and discussion.The theories applied in this study are: translation equivalence suggested by Catford, and Translation as retextualization by Coulthard and Halliday theory within the perspective of Systemic Functional Linguistics, called the ideational function which is realized by the transitivity system.The finding suggests that as far the transitivity system of SIL in ST and TT is concerned; WS’ most significant characteristics were kept unchanged. There were moments in which some changes took place because of the structure of the language in which the text was retextualised. Nevertheless, these changes, at a micro level, do not modify the characters’ construction at a macro level.Through the analysis of the transitivity patterns, it can be said the ST and the TT selected and realized similar meanings thus constructing similar pictures of the main protagonist, William Shakespeare.